Promoting digital inclusion through public-private partnerships for older adults in Nigeria: A review - Judith Ifunanya ANI; Kezia Batisai (Aging and Health Research)
In the face of global demographic shifts and rapid digitalization, ensuring digital inclusion for the aging population is imperative. Projected to reach 1.5 billion by 2050, older adults stand at the intersection of societal challenges and digital opportunities. The review emphasizes the multifaceted role of digital inclusion, aligning with the World Health Organization's Global Strategy on Ageing and Health and supporting Sustainable Development Goals 3, 4, and 10. Despite the potential benefits, the digital divide persists in developing countries like Nigeria, accentuated by limited technology access. Urgent research is needed to understand technology acceptance among older adults, highlighting the necessity for public-private partnerships to bridge these gaps. The comprehensive approach advocates for inclusive policies, technological advancements, and collaborative efforts, ensuring older adults are not left behind in the evolving digital landscape.